Improving the energy storage performance of BaTiO3-based glass ceramics by reconstituting glass network structure via electronegativity tuning - Juwen Wei; Fei Shang; Haibo Zhang; Guisheng Zhu; Yunyun Zhao; Guohua Chen; Zuo-Guang Ye; Jiwen Xu (Journal of Materiomics, 2025)
Developing dielectric capacitors with both excellent recoverable energy storage density (Wrec) and high dielectric breakdown strength (DBS) are highly desired for pulsed power electronic systems. Although glass ceramics are known to potentially possess simultaneously a high DBS and a relatively high dielectric constant (εr), it is still a long-standing challenge to obtain high energy storage performance in glass ceramics. In this work, based on the consideration of electronegativity and its effects on the degree of polymerization, SnO2 addictive was introduced to reconstitute the parent glass network structure and thereby an ultra-high DBS value of 2809 kV/cm was achieved in the SnO2-doped parent glass. After crystallization of the SnO2-doped parent glass, an ultrahigh Wrec of 10.13 J/cm3 with an efficiency (η) of 85.5% and a superb discharge energy storage density (Wd) of 9.09 J/cm3 at 1500 kV/cm were obtained in the BaTiO3-based glass ceramic. Meanwhile, this BaTiO3-based glass ceramic displays a good thermal stability over a wide temperature range of 30–120 °C, with the Wrec only decreasing by 3.0% and Wd dropping from 4.40 J/cm3 to 3.53 J/cm3 at 800 kV/cm. Furthermore, it also exhibits high optical transmittance (about 60%) in the visible light spectrum. These features indicate that the BaTiO3-based glass ceramic studied in this work has a great potential not only for high-pulsed power applications but also for optical applications, making it a truly multifunctional material.